Women and aging : an international, intersectional power perspective - Muhlbauer, Varda; Chrisler, Joan C.; Denmark, Florence L. (Springer International Publishing : Imprint: Springer, 2015)
These are paradoxical times to be an older woman . As individual older women take the stage as role models in the arts and the public sphere, female elders as a group are marginalized as dependent, declining, and unimportant. Women and Aging surveys the evolving sociopolitical landscape in an era still struggling with gender and age discrimination. This insightful volume recasts familiar concepts such as social roles, appearance, health, sexuality, and transition through the related lenses of empowerment/restraint and quality of life/well-being for a deeper understanding of the disparities that exist both with men and within their own gender. Two especially relevant questions emerge from this framework: how women over 60 are contributing to the current climate of societal change, and how these positive developments can improve the lives of older women as a whole. Featured topics analyze the wider implications of older women's experiences as family members, sensual and sexual beings, drivers of economies, and members of a diverse population worldwide:  Older women, power, and the body. Older women, economic power, and consumerism. The impact of multiple roles on older women: Strain or enrichment? Older women, leadership, and encore careers. Sexuality in older women: Desirability and desire. Lesbians over 60: Newer every day. Clinical interventions to empower older women. A significant advanc e in feminist research, Women and Aging brings path-breaking perspectives to scholars in women's studies, gerontology, psychology, sociology, social work, and human development, whether they study women who have overcome barriers or those who need support in changing the rules.